(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2021)
Meanders are one of the common features of flat areas’ channels of many rivers. They are characteristic for the largest rivers originating from Armenian Highland (Euphrates, Tigris, Kura, Araks, etc.) where they leave the mountainous territories and enter the adjacent plains. There are highland rivers meanders studies only for the territory of Iraq: but there is no information regarding meanders’ parameters. Meanders of the largest highland rivers form not only valley bends caused by volcanic massifs flow and mountain ranges or sharp shift of valleys as a result of tectonic shifts, but also channel bends (meanders) formed by actual water flow within floodplains. The deviation of riverbeds from their initial stretch is also noted by growing proluvial cones of tributaries, landslide «tongues», rockfalls, mudstone outflows. Free (wandering) meanders of the riverbed and the accompanying ox-bows are formed mainly on flat uplands near rivers with clay or loamy banks bearing much sediment in a state of dynamic equilibrium. Large and clearly defined free meanders of Euphrates River were formed only within the plains of Syria and Iraq. Tigris River has free meanders mainly in Mesopotamian lowland, and Kura River-mostly within Kura-Araks lowland. The meanders of Araks River mostly belong to forced varieties. The meanders’ parameters are determined: the width of the meandering belt, the bend pitch, the bend deflection boom. Meanders and ox-bows as well as the meandering belt are clearly distinguished in high-resolution color satellite images by the green color of floodplain vegetation, in particular, in images on the territory of Syria. For all largest rivers of the highlands and their large tributaries in the areas of accumulation the fragmentation of the channel into arms the formation of sandy or sandy-pebble islands is characteristic.